Penerapan guided writing untuk meningkatkan keterampilan menulis deskripsi pada peserta didik kelas II sekolah dasar - Aprilia Eka Kartikasari (Didaktika Dwija Indria, 2023)
This study aims to improve description writing skills by applying guided writing. This study is Classroom Action Research with two cycles. The subjects in this study were the second grade students of state Primary School of Tegalrejo 98 Surakarta in academic year 2019/2020 with 15 students. Data collection techniques in this study in the form of interviews, observations, tests and documentations. Validity test technique in this study are the source and content triangulation technique, as well as the content validity. Data analysis used is interactive analysis and comparative descriptive analysis. The initial condition of descriptive text writing skills of second grade resulted 13,3%. The first cycle resulting in percentage of 46,7% in classical and the second cycle with the percentage of 86,7% in classical terms. The conclusions in this study is guided writing improved descriptive writing skills on second grade students of state Primary School of Tegalrejo 98 Surakarta 2091/2020 academic year.